A provisional UniGene clone set based on ESTs from Neurospora crassa - William H Dvorachek Jr; Patricia L Dolan; Mary Anne Nelson; Donald O Natvig (Fungal Genetics Reports, 2001)
We have constructed a list of N. crassa cDNA clones for which partial sequences exist, toward the goal of maximizing the number of genes represented while avoiding redundancy. This effort employed GenBank sequences from the combined N. crassa EST projects at the University of New Mexico, the University of Oklahoma and Dartmouth College (27,557 ESTs; Nelson et al. 1997 Fungal Genet. Biol.21:348-363; Zhu et al. 2001 Genetics 157: 1057-1065). The current list, subject to ongoing revision, includes 2842 clones and is available at the web site of the Neurospora Genome Project (NGP) at the University of New Mexico (http://www.unm.edu/~ngp/), along with details of its construction. Each cDNA clone in the list represents a unique gene. We have also assembled a UniGene set of cDNA clones for that portion of the UniGene set that is represented in libraries constructed by the NGP at UNM. This UniGene library is comprised of 1786 clones distributed in 20 96-well dishes, and it is available through the Fungal Genetics Stock Center.